A DISTRIBUTED MODEL TO IMPROVE QUALITY OF SERVICE (QoS) PERFORMANCE OVER THE FIXED WIMAX NETWORK - LAWAL, IBRAHIM ALHAJI (2014)
Worldwide Interoperability for Microwave Access (WiMAX) technology is a preliminary step to develop Fourth Generation networks (4G) technologies. It has not only succeeded in the utilization of several of the latest telecommunication techniques in the form of unique practical standards, but also paved the way for tbe quantitative and qualitative developments of high-speed broadband access. The IEEE 802.16 Standard introduces several advantages; one of them is support for Quality of Services (QoS) at the Media Access Control (MAC) level.